1999
DOI: 10.1055/s-1999-3672
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Chromium(II)- and Chromium(III)-Mediated Organic Synthesis

Abstract: Synthetic transformations utilizing chromium(II) or chromium(III) reagents, mainly CÐC-coupling reactions, are discussed. Chromium reagents find increasing application in complex total syntheses where other organometallics are difficult to apply. They are easy to prepare and exhibit extraordinary chemoselectivity and high diastereoselectivity. In this article emphasis is laid on recent results in synthetic procedures, on little known general aspects of (organo)chromium chemistry, and on areas not reviewed befo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
55
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(57 citation statements)
references
References 173 publications
(337 reference statements)
1
55
0
1
Order By: Relevance
“…[3,10 ± 18] Interestingly, an OMPV-reaction also seems to participate in other chromium(II)-mediated reactions like the Nozaki±Hiyama À Kishi and chromium-Reformatsky reactions. [3,5,8] In accordance with this observation, OMPV equilibria are especially relevant in products from substituted allylchromiums, whereas good enantioselectivities were initially reported for the unsubstituted case only. This prompted us to look more closely into the relationship between enantioselective Nozaki±Hiyama reactions and OMPV transformations.…”
mentioning
confidence: 71%
See 2 more Smart Citations
“…[3,10 ± 18] Interestingly, an OMPV-reaction also seems to participate in other chromium(II)-mediated reactions like the Nozaki±Hiyama À Kishi and chromium-Reformatsky reactions. [3,5,8] In accordance with this observation, OMPV equilibria are especially relevant in products from substituted allylchromiums, whereas good enantioselectivities were initially reported for the unsubstituted case only. This prompted us to look more closely into the relationship between enantioselective Nozaki±Hiyama reactions and OMPV transformations.…”
mentioning
confidence: 71%
“…[1,2] An elegant method for the synthesis of homoallyl alcohols is the chromium(II)-promoted Nozaki±Hiyama reaction, which allows the coupling of allyl halides with aldehydes in a Barbier-type reaction. [3,4] In our previous studies on the Nozaki±Hiyama reaction we observed that allyl ketones 4 can be common side products, or even the main product, although they are neglected by most authors. [5] This formation can be explained by an Oppenauer-type oxidation mechanism (Scheme 1) and is strongly favoured with sterically unhindered aromatic aldehydes and a substituted allylchromium.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…31 Second, the rate of hydrolysis of chromiumcarbon bonds is relatively slow, in sharp contrast to the other metalcarbon bonds of early transition metals. 32 Therefore, addition reactions of organochromium reagents to carbonyl compounds do not require strictly anhydrous conditions. By taking this as an opportunity, nucleophilic organochromium reagents could be generated by addition of an equimolar amount of water; though slow addition of the water is required (Scheme 19).…”
mentioning
confidence: 99%
“…13,32,34 1.3 Geminal Dimetallic Reagents for Olefination of Carbonyl Groups: Organotitanium Reagents.…”
mentioning
confidence: 99%